Using enzymes to improve frozen-dough bread quality - Lin, Hsing-I (Kansas State University, 2008)
Potassium bromate is a well-known strong chemical oxidant. It was once widely used by the baking industry all over the world, especially for making frozen doughs. Since potassium bromate has been banned in many countries, many researchers have studied in this area to find a replacement. Ascorbic acid was often combined with potassium bromate in frozen dough making as an oxidant dough additive. In addition, ascorbic acid has different chemical oxidant activity, and its function in yeast leavened dough is not as strong as is potassium bromate. More dough additives have been found, such as enzymes. Enzymes play key roles in bread making. In recent years, enzyme usage in bread making has been increasing, especially for shelf-life extension. Based on the results from this research, potassium bromate use can be replaced by a combination of ascorbic acid and hemicellulase/endoxylanase. However, using hemicellulase/endoxylanase alone cannot benefit frozen dough quality such as finer crumb cell or increasing final bread volume. These experimental results also show that using a combination of ascorbic acid and hemicellulase/endoxylanase can delay the development of bread firmness (staling) after baking. As frozen storage time increased, the firmness of frozen dough bread increased, and the bread tended to have a coarser texture. Hence, larger and uneven grain cells reflect a gray or dark crumb color.
Keywords: dough; frozen; bread; quality; enzyme; Agriculture, General (0473); Health Sciences, Nutrition (0570); Home Economics (0386)